Inclusión excluyente: narrativas del profesorado de educación básica y enseñanza a estudiantes mapuches: Exclusionary Inclusion: Narratives of Basic Education Teachers and Teaching Mapuche Students - Bravo Villa, Ninosca Carmen; Mariñanco Nahuelcura, María Isabel (Universidad del Zulia, 2021)
This article studies the narratives of teachers who work in basic schools located in Mapuche-Lafkenche territory in the La Araucanía region. The research problem addresses the intersection between inclusion and interculturality based on the practices narrated by the teachers. The method used was qualitative with descriptive scopes. The design was an instrument-type case study. Semi-structured interviews were applied, which were coded in an open and axial way with the qualitative software Atlas ti 8.0. The main findings indicate that the narratives show symbolic, cultural, pedagogical and linguistic violence reproduced by the teachers in the education of the Lafken-mapu boys and girls, which reflects that the knowledge of the western Chinese curriculum is the one that is preferably mobilized in classrooms with indigenous population.